2014
DOI: 10.1016/j.jsat.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Is level of exposure to a 12-step facilitation therapy associated with treatment outcome?

Abstract: This study examined whether level of exposure to Stimulant Abuser Groups to Engage in 12-Step (STAGE-12), a 12-Step facilitative therapy, is related to treatment outcome. Data were from a large National Drug Abuse Treatment Clinical Trials Network (CTN) study comparing STAGE-12 combined with Treatment-as-Usual (TAU) to TAU alone. These analyses include only those randomized to STAGE-12 (n = 234). Assessments occurred at baseline and 30, 60, 90, and 180 days following randomization. High-exposure patients (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The robust association of longer retention with better outcomes in substance abuse treatment has been extended to TSF treatment (Katsukas et al, 2009; Wells et al, under review), supporting the importance of treatment retention for TSF. The current study contributes to recommended research on treatment variables as predictors of retention (Brorson et al 2013; Swift & Greenberg, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The robust association of longer retention with better outcomes in substance abuse treatment has been extended to TSF treatment (Katsukas et al, 2009; Wells et al, under review), supporting the importance of treatment retention for TSF. The current study contributes to recommended research on treatment variables as predictors of retention (Brorson et al 2013; Swift & Greenberg, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…TSF participants had higher rates of attendance and involvement in 12-Step programs post-treatment and at 6-month follow-up. The relationship of number TSF treatment sessions attended (using a dichotomous measure called high versus low exposure) to participant outcomes was also examined (Wells et al, under review). High exposure to treatment, defined as attendance at two or more (out of 3) individual sessions plus three or more (out of 5) group sessions, was achieved by 77% of TSF participants and was associated with a) significantly higher odds of abstinence from stimulants during treatment and across 4 months of follow-up, b) significantly lower rates of stimulant use for non-abstinent participants and non-stimulant drug use during treatment, but not after, and c) more days of attending 12-Step meetings and engaging in duties during meetings through 90-days post treatment (Wells et al, under review).…”
Section: Treatment Retention and Outcomes In Tsfmentioning
confidence: 99%
“…Groups such as Alcoholics Anonymous, Women for Sobriety, Narcotics Anonymous, SMART Recovery, Al-Anon, and Nar-Anon offer individuals consistent accountability, mentorship, and mutual aid (54). Research has shown that self-help groups teach effective treatment techniques that are critical to improve substance use outcomes (71)(72)(73)(74).…”
Section: Referrals For Treatmentmentioning
confidence: 99%
“…Comparable to the parent study (Donovan et al, 2013), the primary outcome in the Wells et al (2014) study was the number of days of stimulant use within six, 30-day windows of assessment. These included the 30 days between randomization and mid-treatment, between mid-treatment and end of treatment, and 4 additional 30-day windows over the subsequent four month follow-up period.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding secondary outcomes in the Wells et al (2014) study, those achieving high exposure (completers) to STAGE-12 compared with those with less exposure (non-completers), demonstrated lower probabilities of stimulant positive urines; higher odds of self-reported abstinence from and lower rates of non-stimulant drug use; lower odds of not attending and higher rates (days) of attending 12-Step self-help groups; greater likelihood of reporting no drug problems; a greater maximum number of days of self-reported duties at meetings; and more types of other 12-Step activities engaged in during 30-day assessment windows. More detailed information concerning the evaluation of additional outcomes between individuals with high (completers) versus low (non-completers) STAGE-12 treatment exposure can be found in Wells et al (2014).…”
Section: Methodsmentioning
confidence: 99%